1987
DOI: 10.1016/s0010-9452(87)80009-6
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of Kinesthetically Guided Spatial Perception

Abstract: The present study measured unimanual kinesthetic discrimination for the right and left thumb angular position of male and female right handers without left handed relatives. Each subject's discrimination threshold and constant error were obtained by the Method of Constant Stimuli. Subjects either made an active movement in assessing the standard thumb angle or were passive while the angle was set by the experimenter. Subjects either reported their decision orally or made a non-verbal movement. A difference was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Although tests on the typical left-side advantage yielded results generally consistent with previous findings for spatial motor tasks (Carnahan and Elliott, 1987;Nishizawa, 1991;Nishizawa and Saslow, 1987), these were inconsistent with predicted outcomes. The CE scores showed a typical left-side advantage in movements estimated at equal lengths as well as at other estimated lengths.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Although tests on the typical left-side advantage yielded results generally consistent with previous findings for spatial motor tasks (Carnahan and Elliott, 1987;Nishizawa, 1991;Nishizawa and Saslow, 1987), these were inconsistent with predicted outcomes. The CE scores showed a typical left-side advantage in movements estimated at equal lengths as well as at other estimated lengths.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have shown that lateralization effects are more evident in finger (e.g., Roy and MacKenzie, 1978;Nishizawa and Saslow, 1987) and foot positioning tasks (e.g., Carnahan and Elliott, 1987) than in arm positioning tasks (e.g., Roy and MacKenzie, 1978). The discrepancy between the extent of observable lateralization effects in the finger (or the foot) and the arm has been explained in several ways (e.g., Carnahan and Elliott, 1987;Nishizawa and Saslow, 1987;Kupers, 1972, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies the absolute matching errors were less for the left than right limb when the same limb provided the reference and matching movements. This result was interpreted as a right hemisphere/left limb advantage in detecting and processing proprioceptive position information (Roy and MacKenzie 1978; Carnahan and Elliott 1987; Nishizawa and Saslow 1987; Riolo-Quinn 1991). However, other studies showed no significant differences in matching performance between the limbs (Wrisberg and Winter 1985; Carson et al 1990a, b; Imanaka et al 1995).…”
Section: Introductionmentioning
confidence: 99%